Green roofs – the innovative solution of ecological problems of megacities (Journal of Geography and Environmental Management, 2017)
The article deals with ecological house as one of the conditions for sustainable development. It was described the structure of the ecological home, produced from natural materials that are safe for human health. For the rational use of nature and the preservation of each plot of land is important to the creation of green areas, which prevent the occurrence of environmental problems. Green roofs are one of the main components of the ecological situation improvement megalopolis. Green roofs protect the building from structural and other damage. Green roofs are a good spot for office workers. In addition, it is a very convenient place for conferences and business meetings. Planting artificial green areas to improve the quality of life of people can solve some environmental problems. The article analyzes the role and the structural elements of green roofs that are innovative solution to the environmental problems of megacities.